2013
DOI: 10.1371/journal.pone.0068540
|View full text |Cite
|
Sign up to set email alerts
|

Action Spectra of Zebrafish Cone Photoreceptors

Abstract: Zebrafish is becoming an increasingly popular model in the field of visual neuroscience. Although the absorption spectra of its cone photopigments have been described, the cone action spectra were still unknown. In this study we report the action spectra of the four types of zebrafish cone photoreceptors, determined by measuring voltage responses upon light stimulation using whole cell patch clamp recordings. A generic template of photopigment absorption spectra was fit to the resulting action spectra in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…It was recently shown that the O-bend component of the VMR is dependent on ocular function [12]. Given our finding that the O-bend response was elicited most readily after illumination with 399nm or 458nm light, we predict that this component of the VMR is predominantly driven by retinal short- or medium-wavelength sensitive cones [9]. The regulation of baseline motor activity by ambient illumination is thought to have both ocular and non-ocular components [12].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…It was recently shown that the O-bend component of the VMR is dependent on ocular function [12]. Given our finding that the O-bend response was elicited most readily after illumination with 399nm or 458nm light, we predict that this component of the VMR is predominantly driven by retinal short- or medium-wavelength sensitive cones [9]. The regulation of baseline motor activity by ambient illumination is thought to have both ocular and non-ocular components [12].…”
Section: Discussionmentioning
confidence: 70%
“…Zebrafish retinal photoreceptors include rods and four different types of cone with distinct spectral sensitivities (UV, short-, medium- and long-wavelength), attributable to expression of 8 different opsins whose absorption maxima span the range 354nm – 557nm [5]. Action spectra for individual cones are broad [9] and the zebrafish retina can sense light across a wide range of wavelengths from <350nm to >600nm. Long term changes in motor activity occurring after the O-bend persist in animals lacking eyes; it is thought that photoreceptors in the zebrafish brain mediate the afferent limb of this component of the VMR [12], but little is known about their properties.…”
Section: Introductionmentioning
confidence: 99%
“…For this, we horizontally divided each of n = 31 images into 5 stripes and calculated the fraction of the total image variance explained by PC2 and PC3 as a function of elevation ( Figure 1E). As our camera was designed for human trichromacy and can therefore only approximate the spectral content available to the zebrafish's tetrachromatic retina [22,23], we next computed the chromatic image statistics in hyperspectral images taken at the same sites as seen by the larval zebrafish.…”
Section: Chromatic Content In Nature Varies With Visual Elevationmentioning
confidence: 99%
“…For the quadricromia in various species of the order Cyprinodontimformes similar evidence exists (see Archer, Endler, Lythgoe, & Partridge, 1987;Endeman, Klaassen, & Kamermans, 2013;Neumeyer, 1992), and this is also true for tetrachromatic color vision in goldfish (see Fratzer et al, 1994;Neumeyer, 1992;Palacios, Varela, Srivastava, & Goldsmith, 1998).…”
mentioning
confidence: 65%